Accounting for organizational misconduct - Szwajkowski, Eugene (Journal of business ethics, 1992)
Organizational misconduct (white collar, corporate and occupational crime, unethical behavior, rule violations, etc.) is an increasingly important social concern. This paper proposes that a necessary step toward preventing and treating such misconduct is the understanding of the explanations, called accounts, given by the actor. We argue that the theorizing and findings in the literature on accounts can be organized into a 2×2 matrix framework. The first dimension centers on whether or not the actor admits that some net harm is done by the act, and the second consists of whether or not the actor admits responsibility. When both are admitted (cell 1), the account is a concession, while denial of both constitutes a refusal (cell 4). Admitting responsibility but not harm equates to a justification (cell 2), and the opposite condition is an excuse (cell 3). Building on this matrix, we specify a typology of explanations within each cell which will highlight inter-cell differences. Finally, we explore the implications of this analysis for managers, regulators, and the public.